Challenging Electoral Integrity: The Constitutionality of the 'Empty Box' Victory in the 2018 Makassar Mayoral Election - Muhammad Akbar; Maisa Maisa (Universitas Negeri Semarang, 2024)
Single-candidate regional elections have recently attracted significant attention, as previous regulations did not adequately address scenarios where fewer than two candidate pairs were running. The 2018 Makassar mayoral election, where the